2016
DOI: 10.1177/2156587215623435
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial Activities of Greek Juniper (Juniperus excelsa M.Bieb.) Against Leishmania major Promastigotes

Abstract: Petroleum ether, chloroform, ethyl acetate, and n-butanol fractions of Greek juniper (Juniperus excelsa M.Bieb. from the family Cupressaceae) were evaluated for antileishmanial activities against Leishmania major promastigotes compared to meglumine antimoniate (Glucantime). In vitro toxicity assay was performed using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide and microplate ELISA reader. Extracts were prepared in ethanol/dimethyl sulfoxide (80/20) at 10 to 0.62 mg/mL. The standard was prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Few studies have shown the in-vitro leishmania promastigocidal effect of J . excelsa M. Bieb [ 44 , 52 ], and also its efficacy in the treatment of CL in an animal model [ 53 ]. Therefore, the current randomized controlled clinical trial has evaluated the efficacy of the leaf extract of this native plant on human CL for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have shown the in-vitro leishmania promastigocidal effect of J . excelsa M. Bieb [ 44 , 52 ], and also its efficacy in the treatment of CL in an animal model [ 53 ]. Therefore, the current randomized controlled clinical trial has evaluated the efficacy of the leaf extract of this native plant on human CL for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Persian Juniper has been shown to have an effect on cell-cycle phases of MCF-7 breast cancer cell line [ 85 ]. Satisfactory antileishmanial activity of Juniperus species have also been demonstrated in a few in-vitro and in-vivo studies [ 44 , 53 , 86 ]. In addition, antioxidant and radical scavenging activities of high content of terpenoids in essential oil and considerable phenolic content in extracts of J .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaf extract with IC 50 = 0.97 mg/mL had the highest efficacy against L. major amastigotes. Similarly, in a research by Moein et al the antileishmanial activity total extract of leaves, fruit, and fractions against promastigotes of L. major at concentrations of 0.625 to 10 mg/mL showed a potent anti-leishmanial effect (22). Since the metabolic pathways, culture conditions, pH, and temperature vary in the amastigotes and promastigotes, the sensitivity to the drug is different.…”
Section: Discussionmentioning
confidence: 93%
“…Greek Juniper has been used by Iranian folk practitioners for a long time (21). In recent studies, the anti-leishmanial activity of leaves, fruit, and fractions of J. excelsa on leishmania promastigotes had a potent effect, moreover, in a clinical trial study, the topical form of J. excelsa was effective against leishmaniasis lesions (22,23). The anti-leishmanial activity of this plant may be regarded as the presence of components, such as alkaloids, monoterpene, diterpene, sesquiterpene, and saponins as well as flavonoids (24,25).…”
Section: Introductionmentioning
confidence: 99%